PENGUKURAN STRIKE DAN DIP DI DESA PADAELO’ KECAMATAN MALLAWA KABUPATEN MAROS SULAWESI SELATAN - Wahyuni, Ayusari; Fuadi, Nurul; Zelviani, Sri; Ayu, Dya; Aminah, Aminah; Azyurah, Zilmi; Nur, Fenty (Universitas Islam Negeri Alauddin Makassar, 2019)
It has been done field lectures to determine Strike and dip in the village in the ELO district, Mallawa Maros South Sulawesi Regency. The purpose of this lecture is to know the value of Strike and dip in the lecture site field. The methods used are methods of discussion, sampling and measurement. The tools used are geological compass, GPS, geological Hammer, ATK and meter. From the results of measurements obtained Strike and DIP N353oE/64o value at the location of the lecture field.